“Analisis Pengaruh Pelatihan dan Kompensasi terhadap Kinerja Karyawan Usaha Mikro Kecil Menengah (UMKM) Studi Pada Industri Kerajinan Shuttlecocks Desa Sumengko Kab. Nganjuk” - Vivi Mayangsari (Jurnal Ilmiah Mahasiswa FEB, 2013)
The research is aimed to analyze effect of training and compensation  simultaneously and partialy  toward human performance  of small and medium enterprises  in the shuttlecocks industry at Sumengko, Nganjuk. For analyze this research are using linear regression analyze. This research are classified in causality or explanatory research. Researcher using 60 person for sample. The research  instrument are using validity test, reliability test and classic assumption test include normality, multicollinearity, and heteroscedasticity assumption. The hypothesis are using F test and t test. Result  of the research are : Both of training and compensation variable simultaneously and partialy toward human performance of small and medium enterprises in the shuttlecocks industry at Sumengko, Nganjuk. Keywords : Training, Compensation, Human Performance.